819 Targeting vasoactive intestinal peptide receptor signaling: a novel approach to enhance anti-tumor response in pancreatic ductal adenocarcinoma. (9th November 2020) - Ravindranathan, Sruthi; Tenzin, Passang; Chandrasekaran, Sanjay; Ware, Brandon; Zaidi, Mohammad; Wang, Shuhua; Dhamsania, Rohan; Zhu, Jingru; Thomas, Susan; Majumdar, Anish; Lesinski, Gregory; El-rayes, Bassel; et al.
Abstract : Background: Pancreatic ductal adenocarcinoma (PDAC), the fourth leading cause of cancer related death in the U.S, has a 5-year survival rate of only 10%. 1 The paucity of T cells in the immune privileged tumor microenvironment (TME) is a major limitation in developing an effective immunotherapy against PDAC. 2 The cancer genome atlas (TCGA) shows that human PDAC tumors express high levels of vasoactive intestinal peptide (VIP), an immunosuppressive neuropeptide (figure 1A), that inhibits effector T cell responses. 3 4 We hypothesized that paracrine secretion of VIP in the TME is a targetable mediator of immune paralysis in PDAC, and that pharmacological inhibition of VIP receptor signaling could enhance anti-tumor responses in PDAC. Methods: VIP levels in plasma or cell culture supernatant was determined via VIP-specific enzyme immunoassay. Luciferase transfected KPC (KPC.luc) cells were injected subcutaneously or orthotopically into the pancreas of C57BL/6, CD4KO, or CD8KO mice from Jackson Laboratories. C57BL/6 mice T cell subsets in were depleted post tumor implantation with anti-CD4 and/or anti-CD8 antibodies. Tumor-bearing mice were treated daily with ANT008, a novel VIP receptor antagonist peptide, and/or anti-PD1 monoclonal antibody (MoAb) for 10 days, starting 7-10 days after implantation. T cells isolated from peripheral blood of PDAC patients were expanded 9 days ex vivo in anti-CD3 MoAb coated plates with 30U/ml IL-2 and either control peptide (scrambled VIP sequence) or ANT008. Survival by VIP and VIP receptor expression from the TCGA was clinically correlated. Results: Increased human and mouse PDAC expression correlates with elevated blood levels (figure 1). While the PDAC cancer cell lines express VIP receptors, ANT008 does not have direct cytotoxic effect on cell growth in vitro (figure 2). However, in orthotopic KPC model, treatment with ANT008 & anti-PD-1 significantly decreased tumor growth rate and burden (figure 3) while increasing the intratumoral levels of CD4 and CD8 proliferating T cells (figure 4) via a T cell dependent mechanism (figure 5). Additionally, in ex vivo cultures of T cells isolated from PDAC patients, ANT008 improved the effector properties of T cells via decreasing expression levels of co-inhibitory molecules and decreasing frequency of regulatory T cells (figure 6). Clinically, VIPR1 receptor expression, but not VIP, provides a survival benefit (figure 7). Conclusions: VIP is a targetable mechanism of immune escape in PDAC. Inhibiting VIP receptor signaling improves effector properties of T cells and synergistically improves the anti-tumor response to checkpoint inhibitors in mouse PDAC models. References: Siegel RL, Miller KD, Jemal A. Cancer statistics, 2020. CA Cancer J Clin 2020;70(1):7-30. Sahin IH, et al. Immunotherapy in pancreatic ductal adenocarcinoma: an emerging entity? Ann Oncol 2017;28(12):2950-2961. Gonzalez-Rey E, Anderson P, Delgado M. Emerging roles of vasoactive intestinal peptide: a new approach for autoimmune therapy. Ann Rheum Dis 2007;66(Suppl 3):iii70-6. Anderson P, Gonzalez-Rey E. Vasoactive intestinal peptide induces cell cycle arrest and regulatory functions in human T cells at multiple levels. Mol Cell Biol 2010;30(10):2537-51.